Depressive symptoms, resilience, and psychological well-being among older adults with non-communicable diseases: A correlational study - Made Dian Shanti Kusuma; Ida Ayu Putri Wulandari; I Gusti Ayu Rai Rahayuni; Anak Agung Ayu Yuliati Darmini (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Older adults with non-communicable diseases (NCDs) are vulnerable to psychological challenges, including depressive symptoms and reduced psychological well-being. Resilience is recognized as a protective factor that may buffer these negative effects. This study aimed to examine the relationships between depressive symptoms, resilience, and psychological well-being among older adults with NCDs. Research Methodology: A quantitative study with a cross-sectional correlational design was conducted among 54 older adults selected using total sampling. Data were collected using standardized instruments: the Geriatric Depression Scale (GDS-15), the Connor-Davidson Resilience Scale (CD-RISC-10), and Ryff’s Psychological Well-Being Scale. Data were analyzed using Spearman’s correlation test to assess relationships between variables. Results: The findings showed significant correlations among all variables. Depressive symptoms were strongly negatively correlated with resilience (r = −0.906; p = 0.005) and psychological well-being (r = −0.860; p = 0.013). Resilience demonstrated a strong positive correlation with psychological well-being (r = 0.835; p = 0.019). These results indicate that higher depressive symptoms are associated with lower resilience and psychological well-being, while higher resilience is associated with better psychological well-being. Conclusion: Depressive symptoms, resilience, and psychological well-being are significantly interrelated in older adults with NCDs. Interventions focusing on reducing depressive symptoms and strengthening resilience may improve psychological well-being. Integrating mental health screening and resilience-based interventions into routine care for older adults is recommended to enhance overall quality of life.